ANALISIS STATUS KEBERLANJUTAN PENGELOLAAN AIR BAKU DI KABUPATEN KONAWE PROVINSI SULAWESI TENGGARA - Surya, Ridwan Adi; Purwanto, M. Yanuar J.; Sapei, Asep; Widiatmaka, Widiatmaka (Bumi Lestari, 2016)
The water supply to support the development and human needs need to be guaranteed for the sustainable condition. Decreased water availability and increased water demand has occurred in Konawe Regency Southeast Sulawesi Province. In order to the management for water supply in Konawe Regency can take place in a sustainable condition, it is necessary to apply the concept of sustainable development through the conservation of water resources. This study aims to analyze the sustainability of the status of water management for sustainable water supply in Konawe Regency, and analyze the important factors that affect the sustainability of water management in the Konawe Regency. The analytical method used is a Multi Dimensional Scaling called Rap-Konawe. The results are expressed in terms of index and status of sustainability. The analysis on the five dimensions indicate that the ecological dimension is sustainable enough (52.36%), economic dimension is less sustainable (36.93%), social dimension is less sustainable (34.16%), technology dimension is less sustainable (35.39%), and institutional dimension is less sustainable (35.39%). There was 12 attributes need to be taken care immediately because of the sensitive affect on the increase of index and sustainability status.
Keywords: sustainability, raw water, MDS, leverage analysis